2007
DOI: 10.1097/01.pep.0000249418.25913.a3
|View full text |Cite
|
Sign up to set email alerts
|

Endurance and Gait in Children With Cerebral Palsy After Intensive Body Weight-Supported Treadmill Training

Abstract: Intensive body weight-supported treadmill training may be an effective intervention for some children with CP who are ambulatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
65
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 36 publications
2
65
1
2
Order By: Relevance
“…The results of this study are consistent with Provost et al, who found significant improvement in velocity of walking and energy expenditure were observed and concluded that treadmill training may be an effective intervention for some ambulatory children with CP [16].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results of this study are consistent with Provost et al, who found significant improvement in velocity of walking and energy expenditure were observed and concluded that treadmill training may be an effective intervention for some ambulatory children with CP [16].…”
Section: Discussionsupporting
confidence: 82%
“…These results also make it necessary to include such approaches in daily therapeutic programs. Our results can be attributed to treadmill training providing opportunity to repetitively train the entire gait cycle and facilitate an improved gait pattern with an increased walking speed and distance [15,16]. Treadmill walking exercise has been associated with increased strength and decreases in energy expenditure [17].…”
Section: Discussionmentioning
confidence: 84%
“…The mobility of these children is often observationally evaluated using standardized scales, including the Physicians Rating Scale (PRS) [5][6][7] and the Gross Motor Function Measure (GMFM) 6,[8][9][10][11] , or by documentation of biomechanical variables, including spatiotemporal gait parameters 10,12,13 . Regardless of the method, the digital camera serves a tool in this process, enabling the performance of patients to be recorded for subsequent analysis.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies reported positive results, and most of them recruited children with spastic CP. 4,8,9,[11][12][13]22 In a systematic review of seven PBWSTT studies on children with CP, five were conducted exclusively on spastic CP, and the strength of evidence was found to be weak. 23 Only two studies targeted at participants with nonspastic type of CP, but the findings were inconclusive.…”
mentioning
confidence: 99%
“…[1][2][3] Recent studies have directed interests in evaluating its effects on children with cerebral palsy (CP). 4,[8][9][10][11][12][13][14] CP is an umbrella term describing a group of permanent but nonprogressive defects or lesions of the brain that occurs during early childhood. 15 Although the condition is attributed to a nonprogressive encephalopathy, its secondary complications change over time causing activity limitations throughout the entire life span.…”
mentioning
confidence: 99%